Teoria prospektów i jej wykorzystanie w wyborze decyzji inwestycyjnej - Dudzińska-Baryła, Renata (Prospect Theory and Its Application in Selecting Investment Decision, 2007)
In the decision theory there are many different assumptions aiding in risky situations. One of such assumptions is prospect theory. It respects subjective appraisal of the value of outcome and its probability. The value function has the "s" shape and reflects changeable attitude to risk taking. In this work there will be compared portfolios created from shares quoted on the Polish stock exchange, which were the best in rankings by expected rate of return, variability coefficient and value of prospect.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1167, s. 42-50